Effect of Foreign Ownership on the Relationship Between Capital Structure and Listed Manufacturing and Allied Firms in Kenya - Lumbasio, Ayiego Jackson; Onsiro, Martin; Abuga, Isaac (Acta Universitatis Danubius. Œconomica, 2025)
Financing decisions are closely linked to investment decisions, as firms require resources to finance the activities that result from investments. Finding a balance between the elements of capital structure is crucial for optimizing the financial value of performance while ensuring long-term sustainability within a dynamic business ecosystem. The NSE, the main stock exchange in Kenya, continues to evolve, reflecting its integration into the broader regional financial systems. After a retrospective review of theories that provide substantial insights into the complex dynamics of capital structure decisions, this study aims to examine the effect of foreign ownership on the relationship between capital structure and financial performance of listed manufacturing and related firms in Kenya.